Analysis of Public Interest in Sport Tourism of Serapung in the District of Empat Lawang - Sumiyanto, Fuad Roin Adi; Manullang, Jujur Gunawan; Handayani, Widya (Journal of Social Work and Science Education, 2023)
This study aims to analyze the public's interest in recreational sports in Empat Lawang Regency. Serapungan tourism sport is one of the unique local recreational and tourism activities in the area. However, the scientific literature that discusses public interest in floating tourism is still limited. Therefore, this study uses a qualitative approach with descriptive research methods to describe the actual situation. Data was collected through document review, such as records of the number of participants taking part in Serapungan tourism sports activities from 2019 to 2023 sourced from the records of the Empat Lawang Regency Tourism Office. This study identified three types of floats in the sport of floats, namely fast floats, ornamental floats, and casual floats. Fast absorption involves participants swimming by floating on two bamboos with the aim of reaching the finish line as soon as possible. Decorative floats involve boats decorated with various shapes and boarded by several people. Relaxing drift involves a sightseeing trip using the inner tube of the car as a boat and following the river flow to the finish point. This research concludes that the local people are interested in sport tourism in Empat Lawang Regency. However, public interest in free sports still needs further research. With a deeper understanding of people's interest in mass sports, this research can provide a basis for local governments, sports institutions and local communities to formulate effective development strategies. In addition, this research also contributes to the understanding of how traditional sports can remain relevant and attractive amidst the developing trends of modern sports.